Kilka myśli o nauczaniu kameralistyki = Selected reflections on teaching chamber music - Werner, Janina (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The paper contains condensed reflections on chamber music, based on years of experiences in this field, both from practice and teaching. The main thesis is that chamber education is an essential part of music education at each level of music schools, because it develops students of all ages and enriches their musical imagination.
Keywords: kameralistyka; edukacja muzyczna; chamber music; music education